Pengaruh Trading Volume Dan Harga Saham Terhadap Return Saham Pada Perusahaan Sub Sektor Farmasi Di BEI - Mexano Hans Gery (CV. ITTC INDONESIA, 2023)
The purpose of this study was to see the effect of trading volume and stock prices on stock returns in pharmaceutical sub-sector companies on the IDX. Trading volume is something that is well-known and much loved by young people who have technological skills in the hope of obtaining maximum profits, over time trading is a source of livelihood, not a few who experience profits and not a few who experience losses and even bankruptcy. This study uses pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population in this study are all pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange 2017-2021, totaling 10 companies. Samples were taken using a purposive sampling technique, amounting to 10 companies. The data analysis technique uses multiple linear regression with a significance level of 0.05. Data processing was carried out using the computer program SPSS 22 for windows. The results of this study found that both variables partially and simultaneously have a significant effect on stock returns. With a sig level below 0.05. The contribution of the two variables trading volume and stock price is 53.3%, while the remaining 46.7% is influenced by other factors not discussed in this study.